From grammar to intentionality, a reading in the hermeneutics of the Qur’anic discourse - Al-Baldawi, Lect. Dr. Jinan Salem Mohamed (Thi Qar Arts Journal, 2022)
The research was concerned with revealing the most important mechanisms of hermeneutics of the Qur’anic grammatical discourse in the light of the principle of intentionality, by studying each of: (grammatical structures and their components, Qur’anic readings, endowment, comma, rank, adverbs, inclusion, Arabic movement, Tanween, number) in this sacred discourse, And the statement of its impact in determining the intention of the speaker, and the research concluded that the science of grammar is not limited to the formal rules that link the signs or components of the sentence, but rather it is an interactive system or science in which the sentence does not separate the text from the meaning and intent that the speaker wants, and also concluded that the intent is a cornerstone. It is essential in the architecture of textual meaning, and that every informative objective in the Qur’anic discourse is generated according to a specific strategy, without which that objective would not be achieved.